The processes of construction, deconstruction and reconstruction of an IFSC English language teacher’s professional identity - Machado, Fernanda Ramos; Gil, Gloria (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2017)
This article presents a qualitative study which aimed at investigating the process of identity construction of Silvana, an English language teacher from the Federal Institute of Santa Catarina (IFSC). In order to do so, data were generated from class observations, ﬁeld notes and an interview and analysis consisted in a long and careful process of reﬂection, subjective interpretation and construction of meanings from the data generated in interaction with the theories that support this study. Regarding the latter, we have drawn mainly on the contributions of Wenger (1998), Connelly & Clandinin (1999) and Gee (2000-2001) who present complementary views regarding the concept and construction of identities. As for the methodology, we aimed at describing the events from an emic perspective in order to gain a deeper understanding of the meanings that events had for the participant. Therefore, data were generated from class observations, ﬁeld notes and an interview with Silvana. Results show that there is a complex web of issues interacting in the process of Silvana’s professional identity construction. The entire process involves a movement of construction, deconstruction and reconstruction of her professional identity and is strongly inﬂuenced by her professional landscape in interaction with previous personal, learning and professional experiences.